RUBRICS TO REFINE TEACHING SKILLS IN MAHTEMATICS AT THE SECONDARY STAGE - Chaurasia, P.K. (SCHOOL SCIENCE, 2014)
Assessment for learning is the process of seeking and interpreting evidence for use by learners and their teachers to decide where the learners are in their learning, where they need to go and how best to get there. Assessment in education refers to any of the many ways in which someone seeks to gain evidence to help them to measure or to make judgements about the quality, quantity or level of a pupil's learning. The emphasis in assessment for learning is on the active engagement of pupils with assessment as an integral component of the learning process. When we think of the learner as an active participant in constructing his or her own conceptualisation of mathematics, we need to come up with an assessment strategy through which we could assess the progress of learner in different dimensions of the concepts. Rubrics divide an assignement into its component parts and provide a detailed description of what constitutes acceptable or unacceptable levels of performance for each of those parts. Keeping copies of individual learners' rubrics can allow us to pinpoint a learner's continuing improvement or weaknesses over time, rubrics showing learner development over time can also allow us to gain a clearer view of teaching blind spots, oimissions, and strengths. In this paper, a detail about different parts of rubrics of has been described. Sufficient number of mathematical illustration has also been provided. It can be a utility tool for teachers to refine their teachings skills in respect of their learners.